Evaluación técnico-financiera de un diseño de broca tipo PDC para la perforación de las formaciones de roca dura en el bloque Piedemonte (2018)
In the present project, the stability and aggressiveness of a PDC bit to drill hard rock in the 8 ½ "section in the Piedemonte Block were analyzed and evaluated through a simulation in the BD3 simulator. At the beginning of the project, the geological generalities of the Piedemonte Block area are described, followed by an explanation of the general operations that are carried out during drilling a well of the area. Then, the characteristics that they own and the parts that make up the PDC drill bits are exposed, as well as brief explanations of the remaining types of drill bits. For the next section, the appropriate characteristics and technologies that the new design must have are studied and chosen to obtain the performance and durability results that are being expected.